Assessment on natural ventilation and pollutant dispersion around sunken squares by transient simulation - Hu, Mengjuan; Zhong, Jiading; Chu, Yujie; Liu, Jianlin (Architectural intelligence, 2024)
Sunken square is a semi-open public space that has been gaining popularity in urban planning and designs. Its semi-open design is beneficial to ventilation of the connected underground spaces, but it is also subject to potential exposure to ground-level traffic pollutants. To evaluate the semi-open design’s influence on the balance between underground ventilation efficiency and the pollutant exposure, this study uses large eddy simulation (LES) to simulate turbulent wind flow characteristics and pollutant dispersion in a typical sunken square. The sunken square is connected to two indoor spaces with single-sided opening, and the design features of staircase and arcade are further tested for their influences on the wind flow field. The air change rate per hour ( ACH , h −1 ) is adopted to quantify the ventilation efficiency of the two connected indoor spaces. Results show that the staircases amplify wind velocities for the indoor spaces but also bring higher pollutant concentrations inside together. Moreover, the design of the arcade at the opening prompts the vortex to shift towards the entrance, leading to a heightened concentration of pollutants. Meanwhile, the effective ACH is mostly contributed by the turbulent diffusion ( ACHt ), while the mean flow ( ACHm ) has much less effect on the ventilation of the indoor spaces. These findings of this study provide references for sunken square design.